Anatomi Tumbuhan Pakan Gajah Sumatra (Elephas maximus sumatranus Temminck) di Taman Nasional Way Kambas - Cholidin, Muhammad Syafi; Dorly, Dorly; Ariyanti, Nunik Sri (Institut Pertanian Bogor, 2024)
Forage plants are one of the main aspects in the conservation management of the Sumatran elephant. Anatomical studies of elephant food plants can provide reference data needed in identifying the diversity of elephant food plants, especially in the studies with faecal samples. This study aims to provide anatomical data of Sumatran elephant feed plants. The observed samples consisted of leaf samples from 24 species and stem samples from four species. Samples were prepared for microscopic paradermal section using the wholemount method. The results showed that rectangular epidermal cell shapes were found in samples of Poaceae leaves, Cyperaceae leaves and stems, and Arecaceae leaves. Stomata with dumbbell-shaped guard cells were only found in Poaceae leaf samples and Cyperaceae leaf and stem samples. The presence of silica cells and cork cells distinguished the Poaceae samples from Cyperaceae. Other leaf samples had qualitative anatomical characteristics that varied based on anticlinal walls of epidermal cells, type of stomata, and trichomes. Quantitative characterization of epidermal cell size; stomatal size, density, and index; and trichome density are used to complete the species description and distinguish species that have the same qualitative characteristics. Keywords: epidermis, paradermal leaf section, stomata, trichome, wholemount method